The pathogenesis and environmental maintenance of Mycobacterium ulcerans - Hoxmeier, John Charles, author; Dobos, Karen M., advisor; Izzo, Angelo A., committee member; Foy, Brian D., committee member; DeGroote, Mary Ann, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2014)
Buruli Ulcer Disease (BUD) is a severe, neglected tropical disease of the skin caused by the acid-fast bacillus Mycobacterium ulcerans. The disease is characterized by necrosis of subcutaneous adipose tissue, and healing with contracture and/or intense scarring of the skin. Little is known about the host response to M. ulcerans from transmission and infection, through the course of disease and resolution. Understanding the host-pathogen interaction is key to development of treatment programs for this neglected disease. In this dissertation, a systems biology approach was used to evaluate a laboratory mouse model of M. ulcerans infection and an analysis of the capability of Anopheles gambiae mosquitoes to maintain and transmit the bacterium is described following the introduction and literature review (Chapters 1 and 2). In Chapter 4, the histology and immune responses in a mouse model that mimics human M. ulcerans infection is described, providing insight into the host response during active infection with M. ulcerans. Specifically, non-toxigenic, virulent M. ulcerans was inoculated into the mouse footpad, and the resulting progression of infection and immune response was characterized in both a wild-type C57BL/6 mouse and an immunodeficient Rag1tm1Mom (Rag-/-) mutant mouse strain. Assessment of the bacterial burden in the mouse as a correlate of the infectious process was documented and demonstrated a persistent or latent feature of infection. Additionally, a mechanism of host immunosuppression was described in immunocompetent animals, in the absence of the toxin mycolatone, highlighting the need for better understanding of virulence determinants employed by the bacilli during infection. Chapter 5 reports an expansion of the mouse model to investigate the transmission of M. ulcerans by a mosquito vector. After exposure to M. ulcerans, larval A. gambiae mosquitoes experienced significant developmental delay, resulting in reduced survival and stunted growth. Adult A. gambiae demonstrated bacterial contamination of their external mouthparts with live M. ulcerans bacteria. The contamination pattern of adult mosquitoes implicates these insects in the mechanical transmission of M. ulcerans. The mouse model from chapter 4 was used to evaluate mosquito borne transmission of the bacillus. Infected mosquitoes were allowed to take a blood meal from mice. The subsequent immune response of the mice was measured for sero-reactivity against M. ulcerans. In addition, larval mosquitoes were documented to readily consume water-borne M. ulcerans, consistent with their feeding mechanism. Thus, larval mosquitoes represent a reservoir or point of environmental maintenance of the pathogen. Chapter 6 details the initiation of a study to investigate the metabolic effects of the exposure of adult mosquitoes to virulent M. ulcerans. The developmental delay and subsequent stunted growth of adult mosquitoes after exposure to M. ulcerans was analyzed through the mass spectrometric investigation of small molecules of metabolism in an attempt to elucidate the biological effects of exposure. In summary (Chapter 7), the availability of a well-defined animal model for BUD provides a valuable tool, which can be used to investigate the specialized pathogenic features of this emerging infection and explore novel disease interventions.
Keywords: emerging; mycobacteriology; neglected; vector-borne; immunology; metabolomics